Risk Factors and Clinical Outcomes of Head and Neck Cancer in Inflammatory Bowel Disease: A Nationwide Cohort Study. Issue 9 (19th May 2018) - Nissen, Loes H C; Derikx, Lauranne A A P; Jacobs, Anouk M E; van Herpen, Carla M; Kievit, Wietske; Verhoeven, Rob; van den Broek, Esther; Bekers, Elise; van den Heuvel, Tim; Pierik, Marieke; Rahamat-Langendoen, Janette; Takes, Robert P; et al.
Abstract: Background: Immunosuppressed inflammatory bowel disease (IBD) patients are at increased risk to develop extra-intestinal malignancies. Immunosuppressed transplant patients show increased incidence of head and neck cancer with impaired survival. This study aims to identify risk factors for oral cavity (OCC) and pharyngeal carcinoma (PC) development in IBD, to compare clinical characteristics in IBD with the general population, and to assess the influence of immunosuppressive medication on survival. Methods: We retrospectively searched the Dutch Pathology Database to identify all IBD patients with OCC and PC between 1993 and 2011. Two case-control studies were performed: We compared cases with the general IBD population to identify risk factors, and we compared cases with non-IBD cancer patients for outcome analyses. Results: We included 66 IBD patients and 2141 controls with OCC, 31 IBD patients and 1552 controls with PC, and 1800 IBD controls. Age at IBD diagnosis was a risk factor for OCC development, Crohn's disease (CD; odds ratio [OR], 1.04; 95% confidence interval [CI], 1.02–1.07), and ulcerative colitis (UC; OR, 1.03; 95% CI, 1.01–1.06). For PC, this applied to UC (OR, 1.05; 95% CI, 1.01–1.06). IBD OCC cases showed impaired survival ( P = 0.018); in PC, survival was similar. There was no effect of immunosuppression on survival. Human papillomavirus (HPV) testing of IBD cases revealed 52.2% (12/23) HPV-positive oropharyngeal carcinomas (OPCs). Conclusion: This study shows that IBD is associated with impaired OCC survival. Higher age at IBD diagnosis is a risk factor for OCC development. We found no influence of immunosuppression on survival; 52.2% of OPC in IBD contained HPV.